Museum-Based History Learning for Schools at the Wereldmuseum Leiden: Educational Activities and the Roles of Teachers and Museum Educators - Argitha Aricindy; Wasino; Aji Sofanudin; Hamdan Tri Atmaja; Atika Wijaya; Endah Sri Hartatik; Suryadi (istory Department, Faculty of Social Sciences, Universitas Negeri Semarang in collaboration with Masyarakat Sejarawan Indonesia (Indonesian Historical Society), 2026)
Abstract: This study examines the educational activities and resources of Wereldmuseum Leiden within the context of formal history education, focusing on how learning is designed before, during, and after school visits. The central question is: what structured learning activities are implemented, and how do they support students’ historical understanding? Using a mixed-methods approach, qualitative data were collected through semi-structured interviews with five teachers and two museum educators, complemented by a descriptive survey of 20 participants involved in museum programs. The study analyzes activity types, timing, learning resources, and collaboration patterns between schools and museum staff. Findings indicate that hands-on workshops, artifact observation, and audiovisual materials are the most frequently used activities, mainly conducted during museum visits. Pre- and post-visit activities remain limited, suggesting weak integration with school curricula. Collaboration between teachers and museum educators is generally informal and inconsistent. This study highlights the need for more systematic partnerships between museums and schools to strengthen the pedagogical impact of museum-based history education. It also contributes to the field by adapting the instrument of Escribano-Miralles et al. (2021) to ethnographic museums with colonial collections, revealing specific challenges such as the underuse of pre/post-visit activities and digital resources in these settings. Abstrak: Penelitian ini mengkaji aktivitas dan sumber belajar di Wereldmuseum Leiden dalam konteks pendidikan sejarah formal, dengan fokus pada perancangan pembelajaran sebelum, selama, dan setelah kunjungan sekolah. Pertanyaan utama penelitian ini adalah: aktivitas pembelajaran terstruktur apa yang digunakan dan bagaimana aktivitas tersebut mendukung pemahaman sejarah siswa? Penelitian ini menggunakan pendekatan mixed-methods. Data kualitatif diperoleh melalui wawancara semi-terstruktur dengan lima guru dan dua edukator museum, serta didukung oleh survei deskriptif terhadap 20 partisipan yang terlibat dalam program edukasi museum. Analisis difokuskan pada jenis aktivitas, waktu pelaksanaan, sumber belajar, dan pola kolaborasi antara sekolah dan pihak museum. Hasil penelitian menunjukkan bahwa workshop berbasis praktik, observasi artefak, dan penggunaan media audiovisual merupakan aktivitas yang paling dominan, terutama selama kunjungan berlangsung. Aktivitas sebelum dan setelah kunjungan masih terbatas, yang menunjukkan lemahnya integrasi dengan kurikulum sekolah. Kolaborasi antara guru dan edukator museum juga cenderung bersifat informal dan belum konsisten. Penelitian ini menegaskan pentingnya kemitraan yang lebih sistematis antara museum dan sekolah untuk meningkatkan dampak pedagogis pembelajaran sejarah berbasis museum. Selain itu, studi ini berkontribusi dengan mengadaptasi instrumen Escribano-Miralles et al. (2021) ke konteks museum etnografi bercorak kolonial, serta mengungkap keterbatasan pemanfaatan aktivitas pra- dan pascakunjungan dan sumber digital.pembelajaran yang bermakna di tingkat lokal maupun global.